Double-site doped P2 type sodium ion battery positive electrode material and preparation method thereof

By performing double-site doping in the positive electrode material of P2 type sodium ion battery, the problems of irreversible phase change at high voltage, poor kinetic performance, severe Jahn-Teller effect and poor air stability are solved, and the structural stability and electrochemical performance are improved.

CN119943927APending Publication Date: 2025-05-06CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510285080.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The positive electrode material of P2 type sodium ion battery has irreversible phase change at high voltage, poor kinetic performance, severe Jahn-Teller effect and poor air stability, resulting in structural collapse, capacity attenuation and mechanical fatigue.

Method used

By performing double-site doping in the positive electrode material of P2 type sodium ion battery, doped metal elements and non-metal elements are introduced at the transition metal layer and anion sites, a material with a chemical formula such as Na0.67Zn0.05Ni0.15Fe0.20Mn0.60O1.95F0.05 was formed. The material is prepared by co-precipitation, solid mixing and calcination.

Benefits of technology

Dual-site doping significantly inhibits structural distortion, improves charge and discharge efficiency, extends the service life of the material, enhances its stability, and significantly improves the performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119943927A_ABST
    Figure CN119943927A_ABST
Patent Text Reader

Abstract

The invention discloses a double-site doped P2 type sodium ion battery positive electrode material and a preparation method thereof, and relates to the field of batteries, the material is a layered positive electrode material, and comprises a transition metal layer and a sodium layer; transition metal sites of the transition metal layer comprise manganese, iron, nickel and doped metal elements, and anion sites of the transition metal layer comprise oxygen and doped non-metal elements; and the sodium layer contains sodium ions, so that the problem of structure collapse in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a dual-site doped P2 type sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] With the continuous advancement of global carbon neutrality, the development of new energy has ushered in new opportunities. The rapid development of sodium-ion batteries has made up for the shortcomings of lithium-ion batteries and complemented lithium-ion batteries. The positive electrode material in sodium-ion batteries is one of the key components that determine battery performance and cost. Many researchers are committed to designing advanced positive electrode materials with high energy density and long cycle stability. In order to find more promising positive electrode materials for sodium-ion batteries, researchers have made many attempts, including metal oxides, Prussian blue analogs, polyanionic compounds, amorphous compounds and organic compounds. Layered P2 phase transition metal oxides are regarded as highly promising materials because of their stable structure, high ionic conductivity and excellent rate performance.

[0003] However, it still faces some challenges to achieve large-scale application: (1) Irreversible phase transition: Under high voltage, an irreversible transition from P2 phase to O2 phase will occur, resulting in structural collapse and rapid capacity decay; (2) Poor kinetic performance: Due to the large radius of sodium ions, the ion insertion / extraction process is slow, resulting in poor rate performance; (3) Jahn-Teller (JT) effect: In the low voltage range, high-spin Mn 3+ The severe JT effect can lead to anisotropic deformation of the MnO6 octahedron, which in turn causes mechanical fatigue and irreversible structural degradation, including sliding, distortion and intracrystalline cracks of the TMO2 layer; (4) Poor air stability: It is easy to be damaged by H + / Na + The exchange reaction occurs with water and carbon dioxide in the air, resulting in the release of sodium ions from the sodium layer. These challenges must be addressed to achieve practical applications of high-performance, durable sodium-ion batteries. Summary of the invention

[0004] The present invention provides a dual-site doped P2 type sodium ion battery positive electrode material and a preparation method thereof, which solves the problem of structural collapse in the prior art.

[0005] In order to solve this technical problem, the present invention provides the following technical solution:

[0006] A dual-site doped P2-type sodium ion battery positive electrode material, wherein the material is a layered positive electrode material, comprising a transition metal layer and a sodium layer; the transition metal site of the transition metal layer comprises manganese, iron, nickel and doped metal elements, and the anion site of the transition metal layer comprises oxygen and doped non-metallic elements; the sodium layer comprises sodium ions.

[0007] Preferably, the doped metal element is selected from at least one of Zn, Mg, Ca or Li, and the doped non-metal element is selected from at least one of F, Cl, Br or I.

[0008] Preferably, the chemical formula of the material is Na 0.66-0.75 T w Ni x Fe y Mn z O u A v , T=Zn, Mg, Ca or Li, w+x+y+z=1, A=F, Cl, Br, I, u+v=2,0 <v<0.1。

[0009] Preferably, the chemical formula of the material is Na 0.67 Zn 0.05 Ni 0.15 Fe 0.20 Mn 0.60 O 1.95 F 0.05 .

[0010] This solution also provides a method for preparing the above-mentioned dual-site doped P2-type sodium ion battery positive electrode material, comprising the following steps:

[0011] S1. preparing a solution: dissolving manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio in deionized water to prepare a transition metal salt solution;

[0012] S2, coprecipitation: adding a mixed aqueous solution of Na2CO3 and NaOH as a coprecipitant dropwise to a transition metal salt solution at room temperature; introducing nitrogen gas during the dropwise addition to remove oxygen from the solution; after the reaction, filtering the obtained precursor and drying it to obtain a precursor solid;

[0013] S3, solid-state mixing: ball-milling the obtained precursor solid-doped non-metallic sodium salt with metal oxide and Na2CO3, and drying the mixed ball-milled material under vacuum conditions;

[0014] S4. Preparation by calcination method: In an oxygen environment, the material is first calcined at 450°C-500°C, and then heated to 800-900°C for a second calcination to obtain the product.

[0015] Preferably, the molar concentration of the transition metal salt in step S1 is 0.5 mol / L.

[0016] Preferably, the mass ratio of Na2CO3 to NaOH in step S2 is (1-3):1; the concentration of the mixed aqueous solution of Na2CO3 and NaOH is 2 mol / L. The reaction time in step S2 is 4-7 hours; the drying temperature is 60-100°C, and the drying time is 8-12 hours.

[0017] Preferably, in step S3, the non-metallic sodium salt is selected from at least one of NaF, NaCl, NaBr or NaI; and the metal oxide is selected from at least one of ZnO, MgO, CaO or LiO.

[0018] By selecting appropriate anions and cations to simultaneously carry out doping modification of the anion site and the transition metal site, dual-site doping will produce a synergistic effect, which can inhibit structural distortion and improve charge and discharge efficiency.

[0019] Preferably, the non-metallic sodium salt is selected from NaF; and the metal oxide is selected from ZnO.

[0020] Preferably, the first calcination time in step S4 is 5-7 hours; the heating rate in step S4 is 3-6° C. / min; and the second calcination time is 8-12 hours.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] In this scheme, the anion site and the transition metal site are doped and modified simultaneously in the P2-type layered oxide positive electrode. The dual-site doping will produce a synergistic effect, which can inhibit structural distortion and improve the charge and discharge efficiency. The dual-site doping can adjust the local electronic structure of the material, improve the strength of the material, thereby extending the service life of the material and enhancing its stability, thereby improving the performance of the sodium ion battery. The dual-site doping strategy significantly improves the P2-Na 0.67 Ni 0.15 Fe 0.20 Mn 0.65 Performance of O2(NFM).

[0023] Taking zinc / fluorine dual-site doping as an example, the doping material P2-Na prepared by coprecipitation, solid-state mixing and calcination 0.67 Zn 0.05 Ni 0.15 Fe 0.20 Mn 0.60 O 1.95 F 0.05(ZNFMF), showed excellent cycle stability and rate performance in electrochemical tests. Dual-site doping optimized the local electronic structure of the material, reduced the valence state of transition metal (TM) elements, enhanced the binding energy between lattice oxygen and transition metal elements, shortened the length of transition metal-oxygen bonds, effectively suppressed structural distortion, and improved the cycle performance and structural stability of the material. In situ X-ray diffraction (XRD) and Raman spectroscopy also confirmed the improvement of the structural reversibility of the material during the cycle process. Nanoindentation tests further showed that during the cycle process, the Young's modulus and hardness of ZNFMF were significantly improved compared with NFM. This study successfully improved the structural stability, electrochemical performance and air stability of sodium-ion battery cathode materials through zinc / fluorine dual-site doping, providing new ideas and methods for the further research and development of sodium-ion battery cathode materials.

[0024] The introduction of highly electronegative F- enhances the interaction between cations and anions, effectively reducing the distortion between adjacent transition metal units, thereby improving the cycling performance. Here, P2-ZNFMF exhibits excellent cycling stability in the voltage range of 2-4.1V (capacity retention is 80% after 200 cycles at 1C rate, 1C = 100mA / g). The structural evolution of P2-ZNFMF after de-sodiumization / sodiumization is highly reversible, involving Ni 2+ / Ni 3+ ,Fe 3+ / Fe 4+ ,Mn 3+ / Mn 4+ Charge compensation mechanisms in redox chemistry and fast sodium ion diffusion kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0026] Figure 1 (a) is the X-ray diffraction pattern;

[0027] Figure 1 (b) is the X-ray diffraction Rietveld refinement result of ZNFMF;

[0028] Figure 1 (c) is the X-ray diffraction Rietveld refinement result of NFM;

[0029] Figure 1 (d) Scanning electron microscope image of ZNFMF: 5 μm scale;

[0030] Figure 1 (e) Scanning electron microscope image of ZNFMF: 1 μm scale;

[0031] Figure 1 (f) High-resolution transmission electron microscopy image of ZNFMF;

[0032] Figure 1 (g) is the selected area electron diffraction pattern;

[0033] Figure 1 (h) Scanning electron microscopy image of NFM: 5 μm scale;

[0034] Figure 1 (i) Scanning electron microscope image of NFM: 1 μm scale;

[0035] Figure 1 (j) is a high-resolution transmission electron microscopy image of NFM;

[0036] Figure 1 (k) is a selected area electron diffraction pattern;

[0037] Figure 1 (l) is the transmission electron microscope-energy dispersive spectrometer (TEM-EDS) element distribution map of ZNFMF;

[0038] Figure 2 (a) is the constant current charge and discharge curve;

[0039] Figure 2 (b) Cyclic performance at 1C rate;

[0040] Figure 2 (c) is the charge and discharge curve of ZNFMF;

[0041] Figure 2 (d) is the charge and discharge curve of NFM;

[0042] Figure 2 (e) is the rate performance in the voltage range of 2 to 4.1 volts;

[0043] Figure 2 (f) is the cyclic voltammetry curve of ZNFMF in the voltage range of 2 to 4.1 V at a scan rate of 0.1 mV / s;

[0044] Figure 2 (g) is the cyclic voltammetry curve of NFM in the voltage range of 2 to 4.1 V at a scan rate of 0.1 mV / s;

[0045] Figure 2 (h) Corresponding differential capacity (dQ / dV) curves of NFM and ZNFMF in the voltage range of 2 to 4.1 V;

[0046] Figure 3(a) is the contour map of the in-situ X-ray diffraction pattern of ZNFMF during the first cycle at 0.2C rate;

[0047] Figure 3 (b) In situ Raman spectrum of ZNFMF during charging from open circuit potential to 4.1 V;

[0048] Figure 3 (c) In-situ Raman spectrum of ZNFMF during discharge to 2.0 V;

[0049] Figure 4 (a) is the X-ray photoelectron spectroscopy (XPS) fitting peak of nickel element of P2-type NFM;

[0050] Figure 4 (b) X-ray photoelectron spectroscopy (XPS) fitting peaks of the iron element of P2-type NFM;

[0051] Figure 4 (c) is the X-ray photoelectron spectroscopy (XPS) fitting peak of manganese element of P2-type NFM;

[0052] Figure 4 (d) is the X-ray photoelectron spectroscopy (XPS) fitting peak of nickel element in ZNFMF;

[0053] Figure 4 (e) is the X-ray photoelectron spectroscopy (XPS) fitting peak of the iron element of ZNFMF;

[0054] Figure 4 (f) is the X-ray photoelectron spectroscopy (XPS) fitting peak of manganese element in ZNFMF;

[0055] Figure 4 (g) is the X-ray photoelectron spectroscopy (XPS) fitting peak of transition metal (TM) elements of zinc 2p orbital;

[0056] Figure 4 (h) is the X-ray photoelectron spectroscopy (XPS) fitting peak of fluorine element in P2-type ZNFMF;

[0057] Figure 4 (i) X-ray photoelectron spectroscopy (XPS) fitting peak of oxygen element in P2-type ZNFMF;

[0058] Figure 5 (a) is the electrochemical impedance spectroscopy;

[0059] Figure 5 (b) Multiple cyclic voltammetry curves of ZNFMF at different scan rates;

[0060] Figure 5(c) Constant current intermittent titration technique (GITT) curves of NFM and ZNFMF and the corresponding sodium ion diffusion coefficients (D Na+ )value;

[0061] Figure 5 (d) NFM model used for first-principles calculations;

[0062] Figure 5 (e) is the projected state density of the calculated NFM;

[0063] Figure 5 (f) ZNFMF model used for first-principles calculations;

[0064] Figure 5 (g) is the calculated projected state density of ZNFMF;

[0065] Figure 6 (a1) is the scanning electron microscope (SEM) image of the cross section of the ZNFMF electrode after 0 cycles;

[0066] Figure 6 (a2) is the scanning electron microscope (SEM) image of the cross section of the ZNFMF electrode after 50 cycles;

[0067] Figure 6 (a3) is the scanning electron microscope (SEM) image of the cross section of the ZNFMF electrode after 100 cycles;

[0068] Figure 6 (a4) is the scanning electron microscope (SEM) image of the cross section of the ZNFMF electrode after 200 cycles;

[0069] Figure 6 (b1) is the scanning electron microscope (SEM) image of the cross section of the NFM electrode after 0 cycles;

[0070] Figure 6 (b2) is the scanning electron microscope (SEM) image of the cross section of the NFM electrode after 50 cycles;

[0071] Figure 6 (b3) is the scanning electron microscope (SEM) image of the cross section of the NFM electrode after 100 cycles;

[0072] Figure 6 (b4) is the scanning electron microscope (SEM) image of the cross section of the NFM electrode after 200 cycles;

[0073] Figure 6 (c) is the testing process of nanoindentation test;

[0074] Figure 6(d) X-ray diffraction patterns of NFM after exposure to humid air for different time periods;

[0075] Figure 6 (e) X-ray diffraction patterns of ZNFMF after exposure to humid air for different time periods;

[0076] Figure 7 (a) The structure of the full cell with ZNFMF positive electrode / / hard carbon negative electrode;

[0077] Figure 7 (b) Cyclic voltammetry curves of ZNFMF positive electrode and hard carbon negative electrode;

[0078] Figure 7 (c) is the constant current charge and discharge curve;

[0079] Figure 7 (d) Rate performance;

[0080] Figure 7 (e) Charge and discharge curves of the full battery device at different cycles;

[0081] Figure 7 (f) Cyclic stability of the full battery device at 1C rate; DETAILED DESCRIPTION

[0082] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0083] Example 1

[0084] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.65:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 0.5 mol / L transition metal salt solution. Then, a mixed aqueous solution (2 mol / L) of Na2CO3 and NaOH in a mass ratio of 3:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the drop addition to remove oxygen from the solution. After 6 hours of reaction, the filtered precursor was dried at 80 ° C for 10 hours. 4.2 g of the obtained precursor solid was mixed with 0.05 g NaF, 0.1 g ZnO and 0.7 g of anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum for 12 hours. In an oxygen environment, the material was first calcined at 500°C for 6 hours, then heated to 900°C at a heating rate of 5°C per minute and calcined for 10 hours to obtain a P2-type layered cathode material product P2-Na 0.67 Zn0.05 Ni 0.15 Fe 0.20 Mn 0.60 O 1.9 5F 0.05 (denoted as ZNFMF).

[0085] Example 2

[0086] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.55:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 1 mol / L transition metal salt solution. Then, a mixed aqueous solution (3 mol / L) of Na2CO3 and NaOH in a mass ratio of 2:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the drop addition to remove oxygen from the solution. After 7 hours of reaction, the filtered precursor was dried at 100 ° C for 8 hours. The obtained precursor solid was mixed with 0.05 g NaF, 0.2 g ZnO and 0.7 g anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum for 12 hours. In an oxygen environment, the material was first calcined at 450°C for 7 hours, then heated to 1000°C at a heating rate of 6°C per minute and calcined for 8 hours to obtain a P2-type layered cathode material product P2-Na 0.67 Zn 0.1 Ni 0.15 Fe 0.20 Mn 0.55 O 1.95 F 0.05 (denoted as 0.1Zn).

[0087] Example 3

[0088] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.65:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 0.8 mol / L transition metal salt solution. Then, a mixed aqueous solution (1.5 mol / L) of Na2CO3 and NaOH in a mass ratio of 1:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the dropwise addition to remove oxygen from the solution. After reacting for 4 hours, the filtered precursor was dried at 60 ° C for 12 hours. The obtained precursor solid was mixed with 0.05 g NaF, 0.1 g ZnO and 0.7 g anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum conditions for 12 hours. In an oxygen environment, the material was first calcined at 550°C for 5 hours, then heated to 800°C at a heating rate of 3°C per minute and calcined for 12 hours to obtain a P2-type layered positive electrode material product.

[0089] Comparative Example 1

[0090] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.65:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 0.5 mol / L transition metal salt solution. Then, a mixed aqueous solution (2 mol / L) of Na2CO3 and NaOH in a mass ratio of 3:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the drop addition to remove oxygen from the solution. After 6 hours of reaction, the precursor obtained by filtration was dried at 80 ° C for 12 hours. The obtained precursor solid was mixed with 0.7 g of anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum conditions for 12 hours. In an oxygen environment, the material was first calcined at 500°C for 6 hours, then heated to 900°C at a heating rate of 5°C per minute and calcined for 12 hours to obtain a P2-type layered cathode material product P2-Na 0.67 Ni 0.15 Fe 0.20 Mn 0.65 O2 (denoted as NFM).

[0091] Comparative Example 2

[0092] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.6:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 0.5 mol / L transition metal salt solution. Then, a mixed aqueous solution (2 mol / L) of Na2CO3 and NaOH in a mass ratio of 3:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the drop addition to remove oxygen from the solution. After 6 hours of reaction, the filtered precursor was dried at 80 ° C for 12 hours. The obtained precursor solid was mixed with 0.1 g ZnO and 0.7 g anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum conditions for 12 hours. In an oxygen environment, the material was first calcined at 500°C for 6 hours, then heated to 900°C at a heating rate of 5°C per minute and calcined for 12 hours to obtain a P2-type layered cathode material product P2-Na 0.67 Zn 0.05 Ni 0.15 Fe 0.20 Mn 0.60 O2 (denoted as ZNFM).

[0093] Comparative Example 3

[0094] First, manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio of 0.65:0.15:0.20 were dissolved in 100 ml of deionized water to prepare a 0.5 mol / L transition metal salt solution. Then, a mixed aqueous solution (2 mol / L) of Na2CO3 and NaOH in a mass ratio of 3:1 was added dropwise to the transition metal salt solution as a coprecipitant at room temperature, with a drop time of 2 hours and a drop speed of 2.5 ml / min. Nitrogen was introduced during the drop addition to remove oxygen from the solution. After 6 hours of reaction, the filtered precursor was dried at 80 ° C for 12 hours. The obtained precursor solid was mixed with 0.05 g NaF and 0.7 g anhydrous sodium carbonate (5% excess to compensate for the loss of sodium during sintering), and the mixed ball-milled material was dried under vacuum conditions for 12 hours. In an oxygen environment, the material was first calcined at 500°C for 6 hours, then heated to 900°C at a heating rate of 5°C per minute and calcined for 12 hours to obtain a P2-type layered cathode material product P2-Na 0.67 Ni 0.15 Fe 0.20 Mn 0.65 O 1.95 F 0.05 (denoted as NFMF).

[0095] Example 4

[0096] The active materials, conductive agent acetylene black and polymer binder (polyvinylidene fluoride; PVDF) prepared in Examples 1-3 and Comparative Examples 1-3 were fully ground in a mortar at a mass ratio of 8:1:1, and then dispersed in an N-methylpyrrolidone (NMP) solvent. The resulting material was evenly coated on an aluminum foil and placed in a vacuum oven at 80°C for drying for 12 hours. The electrode was cut into round pieces with a diameter of 12 mm. The battery was assembled in a glove box with an argon atmosphere. In the half-cell, metallic sodium was used as both a counter electrode and a reference electrode. A glass microfiber filter (GradeGF / F) was used as a diaphragm. The electrolyte consisted of 1MNaClO4 dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and 2.0% of fluoroethylene carbonate (FEC) was added. CR2032 button half-cells were assembled in a glove box filled with argon. The constant current charge-discharge and constant current intermittent titration technique (GITT) tests were performed using a new well battery test system (CT4008) in the voltage range of 2.0-4.1 V. The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were measured using an electrochemical workstation DH7000.

[0097] The crystal structure of the obtained samples was analyzed using a powder X-ray diffractometer (XRD, Bruker D8Advance, Germany) with a step size of 0.02° and a scanning rate of 5° / min. During the first cycle, in-situ XRD tests were performed at a scanning speed of 2° / min using a special cell equipped with an X-ray window. The test data were fitted using MDIjade9.0 and corrected using GSAS-II academic software. The morphology, microstructure and elemental composition of the samples were tested using a field emission scanning electron microscope (FESEM) and a transmission electron microscope (TEM). The structural changes of the materials were studied using in-situ Raman technology (Raman spectrometer). The valence states of the elements in all samples were analyzed using X-ray photoelectron spectroscopy (XPS). The elemental ratios of the target materials were studied using an inductively coupled plasma emission spectrometer (ICP-MS). The Ar + The milling system polished the positive electrode sheet for 40 minutes at an accelerating voltage of 6 kV to prepare cross-sectional slices. The maximum load (5000 nm), modulus and hardness of the sample were characterized using a nanoindenter.

[0098] The X-ray diffraction (XRD) results of the prepared NFM, ZNFM, NFMF, 0.1Zn and ZNFMF sodium ion battery layered cathode materials are shown in Figure 1 (a) The XRD spectrum shows that all diffraction peaks correspond to the P2 phase with a hexagonal crystal structure and a space group of P63 / mmc, corresponding to P2-Na 0.67 Ni 0.33 Mn 0.67O2 (JCPDS No. 54-0894). Figure 1 As shown in (a), the doping of Zn / F elements causes the characteristic peak (002) of the P2 phase to move to a lower angle. This shift indicates that the c-axis lattice spacing increases, which is beneficial to the kinetic performance of sodium ions during the cycle. In order to further explore the success of the bulk doping modification of the positive electrode material, the X-ray diffraction data was theoretically corrected using the GSAS-II software. The results are shown in Figure 1 (b) and Figure 1 (c) is shown. Figure 1 Compared with the refined Rietveld result of NFM in (c) (Rp = 3.654%, Rwp = 5.916%), Figure 1 The results of ZNFMF in (b) (Rp = 3.136%, Rwp = 4.753%) are in better agreement with the standard data, indicating that the experimental error is small. The refined crystal structure of ZNFMF (comprehensive crystallographic details, including lattice / isothermal parameters and atomic positions) shows that Zn ions occupy transition metal sites (Wycoff2a sites) in the octahedral layers, while F ions occupy oxygen sites (Wycoff4f sites). In the P2 structure, the Mn-O layers are composed of edge-sharing MnO6 octahedral chains and stacked in an ABBA-type sequence along the c direction. Sodium ions are located at two different positions between these Mn-O layers. Compared with the NFM sample In comparison, the unit cell parameters of the ZNFMF sample are slightly reduced in the a and b axis directions and increased in the c axis direction. Since the ionic radius of Zn (approx. ) is greater than Mn (approx. ), the substitution of Zn for Mn results in an increase in the c-axis length, reflecting changes in the microstructural transport channels. The enlargement of these channels significantly improves the Na + The kinetics of the transport of F was improved, thereby improving the rate performance of ZNFMF. The successful introduction of F into the O site resulted in a decrease in the lattice parameter, which was attributed to the strong electronegativity of F changing the bond energy of O atoms, causing the local collapse of the crystal structure, thereby reducing the crystal volume of the material. to ZNFMF The relative volume reduction is helpful to improve the structural stability and cycle stability.

[0099] F- and Zn 2+ The doping of NFM significantly affects the morphology of the material. Scanning electron microscopy (SEM) observations show that Figure 1 (h) and Figure 1 (i)) compared to the surface of ZxNFMF (x = 0.05, 0.1) (as shown in Figure 1 (d) Figure 1(e)) is smoother and has better particle uniformity, which helps to improve the electrochemical stability. It is worth noting that in the ZxNFMF material, when the Zn content increases from 0.05 to 0.1, a large number of non-uniform particles are observed, resulting in a decrease in crystallinity. In general, when x = 0.05, moderate Zn / F co-doping can improve the material morphology. High-resolution transmission electron microscopy (HRTEM) images of ZNFMF are shown in Figure 2. Figure 1 (f) shows obvious lattice fringes. The measured d spacing of these fringes is The high-resolution transmission electron microscopy image of NFM is shown in Figure 2. Figure 1 As shown in (j), the measured d spacing of these fringes is also, Figure 1 The selected area electron diffraction shown in (g) shows a uniform hexagonal structure, confirming the good crystallinity. Figure 1 (g) shows that the exposed crystal planes of ZNFMF are similar to those of P2-type NFM (e.g. Figure 1 (k) is the same, which indicates that Zn / F dual doping does not destroy the original crystal structure of the material. In order to study the distribution of elements in the positive electrode material, transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS) analysis was carried out. The results are shown in Figure 1 (l) shows that the elements Na, Zn, Ni, Fe, Mn, O, and F are uniformly distributed in the particles of ZNFMF and NFM samples. As shown in Table 1, inductively coupled plasma (ICP) analysis confirmed the expected ratio of Zn:Ni:Fe:Mn in ZNFMF to be 0.0491:0.1502:0.2023:0.5984.

[0100] Table 1

[0101] element Zn Ni Fe Mn Molar ratio (%) 4.91 15.02 20.23 59.84

[0102] The materials were evaluated in the voltage range of 2.0–4.1 V relative to Na + / Na electrochemical performance, verifying the effectiveness of the dual-site doping method. Figure 2 (a) The constant current charge-discharge (GCD) curve shows that at 1C rate, the initial discharge capacity of ZNFMF is 115.95 mAh g -1 The initial discharge capacity of NFM is 116.02 mAh g -1. Compared with NFM, the GCD curve of ZNFMF did not change significantly after three cycles, while the curve of NFM was significantly shortened. These results indicate that the improved stability of ZNFMF is due to the successful doping of zinc / fluorine, which effectively suppresses the irreversible phase transition. The NFM material undergoes more violent irreversible redox reactions of oxygen, destroying the interlayer structure and causing its capacity to decay rapidly. When the zinc doping content increases to 0.1, the voltage platform around 4.05V completely disappears, and the initial capacity of the material decreases to 89.9mAhg-1. The capacity loss is attributed to the increased electrochemical inertness of zinc and the decreased activity of manganese. Figure 2 (b) shows the two materials cycled 200 times at a current density of 1C. The cycle stability of the ZNFMF positive electrode material has been improved, and the capacity retention rate after 200 cycles is 80.15%, which is significantly better than NFM (the capacity retention rate after 200 cycles is 52.7%). Compared with other materials, the cycle performance of the ZNFMF material is also the best. Increasing the zinc content to 0.1 will result in a decrease in capacity and capacity retention (74.8% after 200 cycles). This also proves that the optimal doping ratio of zinc element is 0.05. In addition, as Figure 2 (c) and Figure 2 As shown in (d), the charge and discharge curves during the cycle process show that the voltage decay of ZNFMF is reduced, which also proves that the energy density of the material is improved. Figure 2 (e) The rate performance of the two materials is shown. The results show that the discharge capacity of ZNFMF is about 134 mAh g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C, respectively. -1 、124mAhg -1 、119mAhg -1 、113mAhg -1 、99mAhg -1 、70mAhg -1 and 62mAhg -1 At all current densities, the discharge specific capacity of ZNFMF is always higher than that of NFM. When the current density is restored to 0.1C, the capacity of ZNFMF is restored to 125 mAh g -1 , highlighting its improved rate capability and stable reversibility. The rate performance of the ZNFMF cathode was compared with other materials, further demonstrating its superior characteristics.

[0103] To investigate the evolution of the electrochemical behavior of the materials, cyclic voltammetry (CV) tests were performed in a sodium half-cell. Figure 2 (f) and Figure 2 (g) shows the first five CV cycles of ZNFMF and NFM electrodes between 2.0 and 4.1 V at a scan rate of 0.1 mVs-1. Figure 1 The dQ / dV results shown in (h) are consistent. Within this voltage window, two main redox peaks are observed for the NFM material at 2.5 / 2.05V and 4.05 / 3.95V, while four pairs of redox peaks are observed for the ZNFMF material at 2.2 / 2.05V, 2.35 / 2.3V, 3.7 / 3.7V and 4.1 / 4.1V. Compared with NFM, the CV curves of ZNFMF overlap well during the cycle, reflecting the high reversibility of ZNFMF materials. The NFM material shows severe fluctuations in the first cycle, which is because the material exhibits strong polarization during the redox reaction, resulting in lattice distortion and destroying the stable structure of the material. In contrast, ZNFMF maintains remarkable stability, further confirming that dual-site doping makes the material structure more stable. In order to understand the stability of ZNFMF materials under a wide voltage window, the cycling stability was measured in the voltage range of 1.5-4.3V at 1C current. After 100 cycles, the discharge specific capacity dropped from 165 mAh g-1 to 110 mAh g-1, and the relative capacity retention rate was 67%.

[0104] In order to study the microstructural changes of P2-ZNFMF during the charge and discharge process, in situ X-ray diffraction (XRD) and in situ Raman spectroscopy were used during the initial cycle. Figure 3 As shown in (a), in the initial cycle, when sodium ions are deintercalated from the material, the (002) and (004) peaks continuously move to higher angles, while the (102) peak moves in the opposite direction, indicating that O 2- -O 2- The repulsive force between them increases, causing the c-axis to expand. + -Na + The in-plane repulsion gradually decreases. When sodium ions are embedded in the material, all peaks return to their original positions, indicating that the material has high reversibility. At the same time, the intensity fluctuations of all peaks are minimal throughout the charge and discharge process, further emphasizing the structural stability of the material. This also indicates that there are no obvious stacking faults. In the Raman spectrum of the original sample, a peak at 596 cm -1 The asymmetric stretching vibration of the MO bond at (A1g) and at 484cm -1 The bending vibration of the OMO bond at (E9) is a typical feature of layered transition metal oxides. Figure 3 (b) Figure 3 As shown in (c), in the first cycle, the peak at 484 cm -1 、596cm -1 and 648cm -1The three main peaks at have excellent reversible changes during the electrochemical process. It can be observed that these peaks almost completely disappear when the voltage pulse is higher than 3.8V, which may be due to the weak interaction between sodium and the transition metal layer during the sodium ion deintercalation process. Nevertheless, during the discharge process, these peaks return to their initial positions.

[0105] To gain a deeper understanding of the mechanism of sodium ion deintercalation in Zn / F-modified layered cathode materials, X-ray photoelectron spectroscopy (XPS) was used to analyze and discuss the oxidation states (charge states) of transition metal (TM) elements in the materials. XPS spectroscopy confirmed the high-purity chemical composition of ZNFMF. Figure 4 (a) Figure 4 (b) Figure 4 (c) shows the XPS fitting peaks of the oxidation states of transition metal elements in NFM. Figure 4 (d) Figure 4 (e) Figure 4 (f) shows the XPS fitting peaks of the oxidation states of transition metal elements in ZNFMF. The identification of different peaks shows that after fluorine doping, Ni 2+ (2P 3 / 2 About 854.26eV, 2P 1 / 2 About 871.68eV) increased from 40.26% to 78.15%. 3+ (2P 3 / 2 About 855.60eV, 2P 1 / 2 About 874.01eV) decreased from 59.74% to 21.85%. 3+ (2P 3 / 2 About 711.13eV, 2P 1 / 2 about 723.99eV) and Mn 3+ (2P 3 / 2 About 641.64eV, 2P 1 / 2 The content of Fe (about 653.94 eV) also increased significantly. 3+ The content of Mn increased from 55.75% to 78.89%, while 3+ The content of Fe increased significantly from 54.74% to 66.75%. 4+ (2P 3 / 2 =714.40eV, 2P 1 / 2 ~727.20eV) and Mn 4+ (2P 3 / 2 ~642.72eV, 2P 1 / 2~652.76eV) decreased from 44.25% to 22.11% and from 45.26% to 33.25% respectively. This phenomenon can be attributed to the incorporation of highly electronegative fluorine, which leads to a decrease in the oxidation state of transition metal elements. Figure 4 As shown in (g), in ZNFMF, the Zn2p spectrum shows a divalent state, and characteristic peaks are observed at 1022.9 eV and 1045.9 eV in the high-resolution spectrum. Figure 4 As shown in (h), the XPS spectrum of ZNFMF also shows the standard peak of fluorine element, further confirming that fluorine has been successfully incorporated into the crystal structure of ZNFMF.

[0106] To further understand the mechanism of Zn / F dual-site doping to enhance the electrochemical performance and structural stability of the cathode, XPS and XRD Rietveld refinement were jointly analyzed. The lattice oxygen spectral information was used to evaluate the chemical environment changes between oxygen and transition metal elements in the layered oxide. Figure 4 As shown in (i), the lattice oxygen binding energy in ZNFMF shifts to higher values ​​compared with NFM, indicating that the introduction of F- reduces the electron density of the oxygen outer layer. As a result, the shielding effect is weakened, leading to an enhancement in the binding energy between lattice oxygen and transition metal elements. This enhancement is manifested as a shorter TM-O bond length (from 1.839nm to 1.824nm). In addition, the stronger electronegativity of F- leads to a closer distance between adjacent transition metal units, effectively suppressing structural distortion and thus improving the cycling performance.

[0107] In order to further investigate the kinetic behavior of the materials, electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and constant current intermittent titration technique (GITT) were used. Figure 5 (a) shows that Zn / F co-substitution accelerates the migration kinetics of Na ions, which may be due to the increase in interlayer spacing by Zn / F dual-site doping. Figure 5 As shown in (b), in the voltage range of 2.0-4.1V, the -1 CV measurements were performed on the ZNFMF material at a scan rate of . With the increase of the scan rate, the ZNFMF showed a good current response, but with the increase of the scan rate, the NFM material showed polarization. In order to further study the transport dynamics, the sodium ion diffusion coefficients of the NFM and ZNFMF samples at different voltages were measured by GITT, as shown in Equation (1).

[0108]

[0109] In the given equation, τ represents the constant flow time. The mass and relative molecular mass of the active substance are expressed as mB (g) and MB (gmol -1). The molar volume of the active substance is expressed as Vm (cm 3 mol -1 ) is represented by S (cm 2 ), and the thickness of the electrode is represented by L (cm). During the current pulse process, the changes in the quasi-equilibrium potential and the battery voltage E are represented by ΔEs and ΔEτ, respectively. The sodium ion diffusion coefficient calculated according to formula (1) was compared, as shown in Figure 5 (c) shows that in the range of 2.0-4.1 V, the sodium ion diffusion coefficient of NFM corresponds to the degree of phase transition and is higher than that of ZNFMF. The results indicate that the suppression of P2-O2 phase transition in ZNFMF may be the reason for its faster sodium ion diffusion coefficient.

[0110] Subsequently, theoretical calculations of NFM and ZNFMF were performed (all calculations were performed using density functional theory methods in the ab initio simulation software package VASP. In order to more accurately describe the d orbitals of transition metals, the GGA+U method was used. The effective U values ​​applied were 6.1 eV for Ni ions, 3.8 eV for Mn ions, 5.3 eV for Fe ions, and 4.0 eV for Zn ions. The energy cutoff of the plane wave basis set was set to 500 eV, and the force convergence criterion during relaxation was ) to understand the enhanced charge transfer mechanism in ZNFMF. The NFM and ZNFMF models used for first-principles calculations are shown in Figure 2. Figure 5 (d) and Figure 5 (f). It can be observed that Figure 5 (e) and Figure 5 As shown in (f), the transition metal state density (DOS) curve near the Fermi level in ZNFMF becomes denser compared with NFM, which means that there are more electronic states available to fill near the Fermi level. Fluorine doping usually introduces additional electrons. Specifically, the valence electrons of F may interact with the d orbitals of transition metals. Due to its high electronegativity, F tends to strongly hybridize with the d orbitals of transition metals (especially Fe), thereby changing their electronic structure. In the P2-type structure, Fe may present a lower oxidation state and its electron cloud becomes more localized, making it highly sensitive to F doping. In this energy range, the energy levels of electrons are more dense, resulting in higher conductivity and enhanced electron transport properties in the material. This also shows that Zn / F co-doping can effectively optimize the local electronic structure and promote the oxidation and reduction of transition metals to achieve maximum capacity contribution by fixing the Fermi level in a suitable position for stable synthesis. This also indirectly proves why ZNFMF materials have higher capacity, better cycle stability and longer life.

[0111] To understand the reason for the excellent performance of ZNFMF, the microstructure of the cross-section of the cycled / uncycled electrode sheets was studied. Figure 6 (a1), Figure 6 (a2), Figure 6 (a3), Figure 6 As shown in (a4), the morphology of ZNFMF has almost no change before and after the cycle, and no cracks are found on the surface or inside. Figure 6 (b1), Figure 6 As shown in (b2), a small number of cracks began to appear after the first 50 cycles. Figure 6 (b3), as the cycle continues, the surface cracks extend into the interior and eventually penetrate the entire particle. Figure 6 (b4), after 200 cycles, there are many obvious cracks distributed on the particles, resulting in the fragmentation of the crystal structure. The presence of cracks on the particles destroys the structural integrity of the positive electrode, accelerates the occurrence of side reactions, and promotes the migration of transition metal ions from the transition metal layer to the electrolyte. The dissolution of transition metals promotes the degradation of the solid electrolyte interface on the positive electrode, further leading to the capacity decay of the material. Structural degradation can also be reflected by changes in mechanical indicators. Therefore, nanoindentation technology is used to evaluate the hardness and Young's modulus during the cycle process to assess the degree of structural damage to the material. Figure 6 The test results in (c) show that the nanoindentation hardness and Young’s modulus of ZNFMF are significantly higher than those of NFM (hardness: 5.27 GPa vs. 4.37 GPa, Young’s modulus: 55.4 GPa vs. 35.2 GPa). Both the nanoindentation test results and the observed morphology emphasize the excellent mechanical properties of ZNFMF.

[0112] For cathode materials, air stability is also an important criterion. In order to study the structural evolution of the materials under humid air conditions, the materials were exposed to an ultra-high humidity environment (relative humidity 98%, 25°C) to study the moisture resistance of NFM and ZNFMF. Figure 6 (d) It was observed that as the exposure time increased, a hydration peak (marked as '*') appeared in the NFM material, and its intensity continued to increase. In addition, all X-ray diffraction peaks pointed to the hydration phase and NaHCO3 (marked as ), which indicates that the material gradually hydrates and some sodium ions diffuse out of the sodium layer. In contrast, for ZNFMF, Figure 6 (e) No obvious hydration peaks were observed in any of the exposed samples, and all X-ray diffraction peaks remained unchanged, indicating that the material is more stable in a humid atmosphere compared to the NFM material.

[0113] Finally, if Figure 7As shown in (a), a complete sodium-ion battery was assembled using ZNFMF cathode material and hard carbon anode material to confirm the feasibility of the designed cathode material. The hard carbon anode provides a reversible capacity of about 276 mAh g at 0.1C rate. -1 , relative to Na + / Na's working potential is about 0.1V, such as Figure 7 (b) Figure 7 As shown in (c), the optimized voltage window is 2.0-4.1 V. Following the charge balance principle of the entire battery, the mass ratio of the positive and negative electrodes is carefully adjusted to 1.9:1. Figure 7 (d) The specific capacities of the full battery at 0.1C, 0.2C, 1C, 2C, 5C and 10C rates are 120.5 mAh g -1 、109.6mAhg -1 、103.4mAhg -1 、91.2mAhg -1 、66.4mAhg -1 、49.6mAhg -1 and 28.9mAhg -1 When the rate returns to 0.1C, the capacity can be restored to 108.5mAhg -1 .like Figure 7 As shown in (e), the initial discharge capacity of the full battery at 1C rate is 95.6 mAh g -1 .like Figure 7 As shown in (f), after 150 cycles, the capacity dropped to 69.7 mAh g -1 , and the capacity retention rate is about 73%. In summary, this ZNFMF / / HC full cell with good electrochemical performance reveals the potential of P2-type ZNFMF cathode materials in practical commercial applications.

[0114] In general, the P2-Na 0.67 Ni 0.15 Fe 0.20 Mn 0.65 The O2 material was modified, and the modified material P2-Na 0.67 Zn 0.05 Ni 0.15 Fe 0.20 Mn 0.60 O 1.95 F 0.05Shows excellent performance. Comprehensive analysis by methods such as X-ray photoelectron spectroscopy (XPS), constant current intermittent titration technique (GITT), and density functional theory (DFT) calculations showed that zinc / fluorine dual-site doping optimized the local electronic structure and promoted the redox reaction of transition metals, thereby improving the electrochemical performance. In situ X-ray diffraction (XRD) and Raman spectroscopy analysis also confirmed that the material has excellent structural reversibility during the cycle process. After the cycle, the morphology of the material cross-section was studied by ion milling, and the results showed that dual-site doping enhanced the strength of the material. In addition, nanoindentation testing confirmed that the hardness of the material has been improved. The improvement in structural strength brings a longer service life and more stable cycle performance to the material.

[0115] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A dual-site doped P2-type sodium ion battery positive electrode material, characterized in that: The material is a layered positive electrode material, comprising a transition metal layer and a sodium layer; the transition metal site of the transition metal layer comprises manganese, iron, nickel and doped metal elements, the anion site of the transition metal layer comprises oxygen and doped non-metallic elements; the sodium layer comprises sodium ions.

2. The dual-site doped P2 type sodium ion battery positive electrode material according to claim 1, characterized in that: The doping metal element is selected from at least one of Zn, Mg, Ca or Li, and the doping non-metallic element is selected from at least one of F, Cl, Br or I.

3. The dual-site doped P2 type sodium ion battery positive electrode material according to claim 2, characterized in that: The chemical formula of the material is Na 0.66-0.75 T w Ni x Fe y Mn z O u A v , T=Zn, Mg, Ca or Li, w+x+y+z=1, A=F, Cl, Br or I, u+v=2,0 <v<0.1。 4. The dual-site doped P2 type sodium ion battery positive electrode material according to claim 3, characterized in that: The chemical formula of the material is Na 0.67 Zn 0.05 Ni 0.15 Fe 0.20 Mn 0.60 O 1.95 F 0.05 .

5. The method for preparing the dual-site doped P2 type sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: S1. preparing a solution: dissolving manganese nitrate, nickel nitrate and iron nitrate in a stoichiometric ratio in deionized water to prepare a transition metal salt solution; S2, coprecipitation: adding a mixed aqueous solution of Na2CO3 and NaOH as a coprecipitant dropwise to a transition metal salt solution at room temperature; introducing nitrogen gas during the dropwise addition to remove oxygen from the solution; after the reaction, filtering the obtained precursor and drying it to obtain a precursor solid; S3, solid-state mixing: ball-milling the obtained precursor solid-doped non-metallic sodium salt with metal oxide and Na2CO3, and drying the mixed ball-milled material under vacuum conditions; S4. Preparation by calcination method: In an oxygen environment, the material is first calcined at 450°C-500°C, and then heated to 800-900°C for a second calcination to obtain the product.

6. The method for preparing a dual-site doped P2 type sodium ion battery positive electrode material according to claim 5, characterized in that: The molar concentration of the transition metal salt in step S1 is 0.5-1 mol / L.

7. The method for preparing a dual-site doped P2 type sodium ion battery positive electrode material according to claim 5, characterized in that: The mass ratio of Na2CO3 and NaOH in step S2 is (1-3):1; the concentration of the mixed aqueous solution of Na2CO3 and NaOH is 2 mol / L. The reaction time in step S2 is 4-7 hours; the drying temperature is 60-100°C, and the drying time is 8-12 hours.

8. The method for preparing a dual-site doped P2 type sodium ion battery positive electrode material according to claim 5, characterized in that: In step S3, the non-metallic sodium salt is selected from at least one of NaF, NaCl, NaBr or NaI; and the metal oxide is selected from at least one of ZnO, MgO, CaO or LiO.

9. The method for preparing a dual-site doped P2 type sodium ion battery positive electrode material according to claim 8, characterized in that: The non-metallic sodium salt is selected from NaF; and the metal oxide is selected from ZnO.

10. The method for preparing a dual-site doped P2 type sodium ion battery positive electrode material according to claim 5, characterized in that: The first calcination time in step S4 is 5-7 hours; the heating rate in step S4 is 3-6° C. / min; and the second calcination time is 8-12 hours.